PENGELOLAAN DANA PENDIDIKAN PENGAWASAN KEUANGAN SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN DI SMP NEGERI DI KECAMATAN CEPU - Rinny Hariyanti; Widya Kusumaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT: Management of education funds and financial supervision are crucial aspects in improving the quality of education in State Middle Schools in Cepu District. This research aims to analyze how the management of School Operational Assistance (BOS) funds and financial supervision can contribute to improving the quality of education. Effective management of education funds involves transparent and accountable planning, implementation and evaluation, in accordance with guidelines set by the government. In this context, good financial supervision can prevent irregularities and ensure that funds are used for optimal educational purposes. The research results show that the participation of all stakeholders, including school principals, teachers and school committees, is very important in the process of managing and monitoring education funds. Apart from that, implementing a good internal control system also plays a role in increasing transparency and accountability in the use of funds. Thus, good management of education funds not only contributes to improving educational facilities and infrastructure, but also to improving the overall quality of education in State Middle Schools in Cepu District. It is hoped that this research will provide insight for policy makers and education practitioners in efforts to improve the quality of education through effective financial management and supervision. Key words: Management of education funds, financial supervision, quality of education.